Integration of Phosphate Solubilising Bacteria, Sulphur Oxidizing Bacteria with NPK on Maize (Zea mays): Phosphate Solubilising Bacteria on Maize (Biological Sciences - PJSIR, 2021)
Deficiency of phosphorus can reduce the yield up to 15-20% and its availability to crop plants is the main issue, particularly in calcareous soils of Pakistan. Micro-organisms, phosphorus solubilizing bacteria (PSB) and sulphur oxidizing bacteria (SOB) have the ability to make P accessible for optimum plant growth, under conditions of nutrients disparity. Therefore, six treatments i.e. control, Yz dose of NPK, full recommended dose of NPK, Yz NPK+ SOB, Yz NPK + PSB and Yz NPK + SOB+ PSB were applied in a field experiment to investigate the integrated role of SOB and PSB with NPK fertilizers for enhancing the maize production. The treatment was concluded to have major impact on agro-morphological traits, seed quality and growth parameters of maize. Results depicted that the use of Yz NPK + SOB + PSB gave maximum germination count/plot (151.33), plant height (189.03 cm), number of ears/plant (1.60), grains/ear (472.33), 1000-grain weight (305.67 g), grain yield (5350.50 Kg/ha), harvest index (31.23%), leaf area (379.77 cm2), total dry matter accumulated (181.43 g/plant), crop growth rate (30.60 g/day), net assimilation rate (9.31 g/day) and protein contents (8.49%).